Pengembangan Aplikasi Pencatatan Layanan Jasa Pernikahan berbasis Mobile (Studi Kasus: Kasiati Wedding) - Fitria Adi Sulistiya Rini; Issa Arwani; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Kasiati Wedding is a wedding service that provides makeup and decoration services for prospective customers who will carry out weddings. There are problems in the ordering process which is still manual using a book. Order data recorded in the book has order dates that are not sequential because the ordering of orders is not based on the order of the date of the message. This makes it a little difficult for the owner and takes time in receiving reservations so the owner needs to make sure in advance to be able to accept new orders. Then, the owner will coordinate with employees to work on the order. Order data will be a reference for employees in making orders from customers, such as the date of the message, the address of the event, and the service ordered. Constraints that arise in employees who often ask the owner again about the order data on the next schedule which has previously been submitted by the owner. To solve this problem, a mobile-based wedding service recording application was developed to manage services by the owner and make it easier to view orders for employees. In developing this application, we utilize the Laravel and React Native frameworks that communicate with the REST API and database implementation using PostgreSQL. Tests carried out using black-box testing and user acceptance testing. Black-box testing resulted in 100% valid from 17 test cases. Meanwhile, user acceptance testing scored 80.5. Based on the test results, the level of user acceptance strongly agrees with the mobile-based marriage service registration application.